On the Weak Convergence of the Extragradient Method for Solving Pseudo-Monotone Variational Inequalities - Vuong, Phan Tu (Journal of optimization theory and applications, 2018)
In infinite-dimensional Hilbert spaces, we prove that the iterative sequence generated by the extragradient method for solving pseudo-monotone variational inequalities converges weakly to a solution. A class of pseudo-monotone variational inequalities is considered to illustrate the convergent behavior. The result obtained in this note extends some recent results in the literature; especially, it gives a positive answer to a question raised in Khanh (Acta Math Vietnam 41:251–263, 2016 ).